TiO2@COF Nanowire Arrays: A “Filter Amplifier” Heterojunction Strategy to Reverse the Redox Nature - Chen, Yong-Jun; Wen, Ying-Yi; Li, Wen-Hua; Fu, Zhi-Hua; Wang, Guan-E; Xu, Gang (Nano letters, 2023)
Surface modification is a promising method to change the surface properties of nanomaterials, but it is limited in enhancing their intrinsic redox nature. In this work, a “filter amplifier” strategy is proposed for the first time to reverse the intrinsic redox nature of materials. This is demonstrated by coating a COF-316 layer with controlled thickness on TiO2 to form core–sheath nanowire arrays. This unique structure forms a Z-scheme heterojunction to function as “a filter amplifier” which can conceal the intrinsic oxidative sites and increase the extrinsic reductive sites. Consequently, the selective response of TiO2 is dramatically reversed from reductive ethanol and methanol to oxidative NO2. Moreover, TiO2@COF-316 provides remarkably improved sensitivity, response, and recovery speed, as well as unusual anti-humidity properties as compared with TiO2. This work not only provides a new strategy to rationally modulate the surface chemistry properties of nanomaterials but also opens an avenue to design high-performance electronic devices with a Z-scheme heterojunction.